The Response of Carabid Beetles (Coleoptera, Carabidae) to Atlas Cedar Afforestation: Insights for Conservation Management from Synecological Models. - SANDRA MELAIKIA; DJIHANE MELAOUHIA (My University, 2025)
In the context of Atlas cedar (Cedrus atlantica) afforestation in Algeria, this study explores the specific and functional composition of Carabidae beetle communities, known for their bioindicator value. Inventories conducted in the cedar forest of M’Cid Ouled Driss (Souk Ahras province) recorded nine species, predominantly predatory (89%) and with a strong affinity for forest habitats (≈78%). A multivariate approach, based on RLQ analysis and the Fourth-corner test, was used to examine the relationships between functional traits (body size, trophic regime, hunting strategy), environmental conditions (altitude, humidity, ground cover), and species distribution. The results reveal a functional structuring along ecological gradients: large visual predators dominate humid forest habitats, while smaller or more specialized species are found in more open environments. Although species richness was lower compared to other Algerian cedar forests, it was offset by a high functional diversity, indicating active ecological processes. The study confirms the central role of Carabidae in forest ecosystem functioning and their sensitivity to climatic variables. It highlights the need for ongoing ecological monitoring based on functional indicators to support restoration efforts and sustainable management of these forest ecosystems. ---------------------------------------------------------------------------------------------------------------------------------- في سياق تشجير الأرز الأطلسي في الجزائر، تكشف هذه الدراسة التركيب النوعي والوظيفي لمجتمعات الخنافس Carabidae، المعروفة بدورها كمؤشر حيوي. حددت عمليات الجرد التي أُجريت في غابة الأرز مسيد أولاد إدريس (ولاية سوق أهراس) تسعة أنواع، معظمها مفترسة (89%)، مع تقارب قوي مع الغابات (≈78%). أتاحت المقاربة متعددة المتغيرات، القائمة على تحليل RLQ واختبار « الزاوية الرابعة »، دراسة العلاقات بين السمات الوظيفية (حجم الجسم، النظام الغذائي ، استراتيجية الصيد)، والظروف البيئية (الارتفاع، الرطوبة، الغطاء الأرضي) وتوزيع الأنواع. تكشف النتائج عن هيكل وظيفي وفقًا للتدرجات البيئية : تهيمن الحيوانات المفترسة البصرية الكبيرة على بيئات الغابات الرطبة، بينما توجد الأنواع الصغيرة أو المتخصصة في الموائل الأكثر انفتاحًا. يُعوّض انخفاض التنوع، مقارنةً بغابات الأرز الأخرى في الجزائر، بثراء وظيفي يُشير إلى عمليات بيئية نشطة. تُؤكد هذه الدراسة الدور المحوري لالخنافس في عمل النظم البيئية الحرجية وحساسيتها للمتغيرات المناخية. وتُسلّط الضوء على الحاجة إلى الرصد البيئي المستمر، استنادًا إلى المؤشرات الوظيفية، لدعم جهود الترميم والإدارة المستدامة في هذه النظم البيئية. ------------------------------------------------------------------------------------------------------------------------------------- Dans un contexte de boisement de cèdre d’atlas Cedrus atlantica en Algérie, une étude explore la composition spécifique et fonctionnelle des communautés de coléoptères Carabidae, reconnus pour leur rôle bioindicateur. Les inventaires réalisés dans la cédraie de M’Cid Ouled Driss (wilaya de Souk Ahras) ont permis de recenser neuf espèces, majoritairement prédatrices (89 %), à affinité forestière marquée (≈78 %). L’approche multivariée, basée sur l’analyse RLQ et le test « Fourth-corner », a permis d’examiner les relations entre traits fonctionnels (taille corporelle, régime trophique, stratégie de chasse), conditions environnementales (altitude, humidité, écologiques : les grands prédateurs visuels dominent les milieux forestiers humides, tandis que les espèces de petite taille ou spécialisées se retrouvent dans des habitats plus ouverts. La faible diversité spécifique, comparée à d'autres cédraies d’Algérie, est compensée par une richesse fonctionnelle révélatrice de processus écologiques actifs. L’étude confirme le rôle central des Carabidae dans le fonctionnement des écosystèmes forestiers et leur sensibilité aux variables climatiques. Met en évidence la nécessité d’une surveillance écologique continue, basée sur des indicateurs fonctionnels, pour accompagner les efforts de restauration et de gestion durable dans ces écosystèmes forestiers.
Keywords: Carabidae; Atlas cedar; functional traits; RLQ; bioindication; trophic diversity; afforestation الخنافس Carabidae، الأرز الأطلسي، السمات الوظيفية، RLQ، المؤشرات الحيوية، التنوع الغذائي، التشجير Carabidae; Cèdre d’atlas; traits fonctionnels; diversité trophique; boisement